Bilateral approach for thoracoscopic esophagectomy with lymph node dissection in the dorsal area of the thoracic aorta in patients with esophageal cancer: A report of two cases. (2017) - Onodera, Yu; Nakano, Toru; Heishi, Takahiro; Sakurai, Tadashi; Taniyama, Yusuke; Sato, Chiaki; Ohuchi, Noriaki; Kamei, Takashi
Highlights: We presented two esophageal cancer patients performed thoracoscopic esophagectomy. These two cases have lymph node metastasis of dorsal area of thoracic aorta (DTA). We performed successfully underwent the dissection of lymph node of DTA. The bilateral thoracoscopic approach performedsafely in the prone position. The long-term outcome of lymphadenectomy in the DTA among esophageal cancer patients remain controversial. Abstract: Introduction: The incidence of lymph node metastasis in the dorsal area of the thoracic aorta (DTA) is relatively low in patients with esophageal cancer. It is difficult to approach the DTA using surgical procedures, such as an open thoracotomy and thoracoscopy in the left decubitus position. Case presentation: Case 1: A 70-year-old man with esophageal cancer underwent thoracoscopic esophagectomy with mediastinal lymph node dissection via a right thoracoscopic approach, followed by lymphadenectomy in the DTA via left thoracoscopy in the prone position. Microscopic findings revealed two metastatic lymph nodes in the DTA. The definitive diagnosis was squamous cell carcinoma of the esophagus, and the pathological stage was T2N3M0 (Union for International Cancer Control [UICC], 7th edition). The patient showed lung metastasis 8 months after the surgery. Case 2: A 72-year-old man with esophageal cancer underwent esophagectomy via a bilateral approach in the prone position, using a similar procedure as in case 1. The definitive diagnosis was squamous cell carcinoma of the esophagus, and the pathological stage was T3N2M0. The patient showed a metastatic mediastinal lymph node 4 months after the surgery. Conclusion: Bilateral thoracoscopic esophagectomy in the prone position can be safely performed, and it might be an alternative curative surgery for esophageal cancer. However, both our cases showed metastasis in the early postoperative period. The long-term outcome and significance of dissection of lymph nodes in the DTA in patients with esophageal cancer remains controversial. Further studies are required to establish the indications and efficacy of this therapeutic approach.